EVOLUTION OF APPROACHES TO TRANSFER PRICING IN THE CONTEXT OF INTERNATIONAL HARMONIZATION OF TAX POLICY: BEPS AS AN INSTITUTIONAL BENCHMARK - Radchenko, Oksana; Polischuk, Рavlo (Український економічний часопис, 2025)
Introduction. In the context of global economic transformation, transfer pricing has evolved from a technical accounting tool to a critical component of international tax governance. Multinational enterprises (MNEs) actively employ transfer pricing mechanisms to reallocate profits across jurisdictions, often exploiting regulatory gaps and tax arbitrage. Purpose. The article aims to conceptualize the evolution of transfer pricing approaches under the influence of international tax harmonization and to analyze the institutional role of the BEPS Action Plan in reshaping regulatory frameworks and fiscal control mechanisms. Methods. The research applies a multidisciplinary methodology, combining comparative legal analysis, economic reasoning, and elements of dialectical logic. Special emphasis is placed on the institutional perspective of transfer pricing regulation in post-BEPS conditions. Results. The study reveals that transfer pricing is no longer a neutral technical practice but a field of strategic interaction between states and corporations. The Ukrainian experience is analyzed in terms of implementation challenges, with focus on domestic schemes such as low-tax jurisdiction exports, inflated import pricing, and internal arbitrage through preferential entities. A risk-based control model is proposed, aligning with OECD standards and emphasizing transparency, digitalization, and fiscal sovereignty. Conclusion. Transfer pricing stands at the intersection of fiscal justice, corporate planning, and global coordination. Its effective regulation requires not only legal clarity but also philosophical and methodological coherence. The institutionalization of the BEPS agenda underscores the urgency of integrating national tax policies into a common global framework without compromising domestic economic priorities.